PENGARUH BOKASHI ECENG GONDOK TERHADAP KANDUNGAN MACRO MINERAL TOP-SOIL LAHAN BEKAS TAMBANG DAN PERTUMBUHAN TANAMAN JAGUNG - Lestari, Wenni Meika; Amelia Lulu Rosalin Hutabarat; Abdul Muta Ali; Rifqi Hidayatulloh; Baluh Medyabrata Atmaja; Evi Wilda Aisya; Alief Rahmania Safitri; Muhammad Irvan Ali (Jurnal Ternak, 2025)
This study investigates the impact of water hyacinth (WH) bokashi applied on stockpiled topsoil from coal mining and utisols areas on maize growth and productivity. Water hyacinth, a locally abundant weed, was processed into bokashi and applied to a mixture of post-mining soil and ultisol at varying concentrations (0%, 12%, 25%, and 50% w/w). Maize plants were cultivated in these media, and growth parameters such as plant height, stem diameter, forage biomass, total biomass, and maize yield were measured weekly. The study employed a Randomized Complete Block Design (RCBD) with four treatments, each replicated four times. Results were analysed using ANOVA and Duncan's Multiple Range Test. The findings demonstrated that WH bokashi could improve the C-organic, nitrogen, P2O5, K2O, and pH levels of the cultivation medium and enhanced maize growth and biomass production. The most effective treatment was 25-50% WH bokashi, which yielded the highest maize productivity. This research highlights the potential of water hyacinth bokashi as an organic amendment for improving degraded soils and supporting sustainable agriculture on reclaimed mining lands.